KETERKAITAN PDRB PERKAPITA DARI SEKTOR INDUSTRI, TRANSPORTASI, PERTANIAN DAN KEHUTANAN TERHADAP KUALITAS LINGKUNGAN DIUKUR DARI EMISI CO₂ DI JAWA TENGAH - Katrin Retno Gupito; Johanna M. Kodoatie (Universitas Diponegoro, 2013)
High economic growth has attracted the attention of economists, researchers, andpoliticians. Economic growth is considered responsible for the degradation of the environment,which emerged as the most significant problems caused by the high economy measured by GDPper capita. This study aims to prove that GDP tends to encourage high environmental degradation,mainly supporters of the four sectors that are discussed in this study.The data used in this study is a secondary data span method (time series), this studyinvestigated the CO2 emission in 30 districts / municipalities in Central Java during the years 2009to 2010 and GDP per capita in 30 districts / municipalities in Central Java in the same. With aspecial focus on the relationship with GDP per capita CO2 emissions to the positive and negativevalues resulting from various sectors such as agriculture, industry, transportation, and forestry.The empirical results indicate a positive and significant relationship between the TransportSector and Forests to Emmision CO2 emissions its 0,04 and Forest Sector to Emmision CO2 its0,00.